Examining the Impact of Rainfall Patterns on Leptospirosis Cases in Bantul District, Indonesia: A Four-Year Ecology Study 2020-2023 - Saadatar Rohmah, Nilna; Samsu Aryanto; Bayu Satria Wiratama (BKM Public Health and Community Medicine, 2024)
Purpose: This study aimed to explore the correlation between rainfall patterns and the incidence of human leptospirosis in Bantul District, Indonesia. Method: The study utilized an ecological design analyzing leptospirosis cases in Bantul District from 2020 to 2023, sourced from the Health Department of Bantul District and Rainfall Trends data from the online central database of the Meteorology, Climatology, and Geophysics Agency (BMKG), especially in Station Climatology DI Yogyakarta. Results: The study identified a total of 489 cases from 2020-2023, with 80 cases of leptospirosis in 2020, 53 cases in 2021, 167 cases in 2022, and 269 cases in 2023 disaggregated towards male (86,91%), than female (13,09%). The majority of leptospirosis patients in Bantul District were middle-aged, with many of them recovering after treatment in various healthcare facilities in the area, although there have been some recorded 43 cases of death. The linear regression analysis revealed a coefficient of 1.3604 (95% CI: 0.758512, 2.962288) and a p-value of less than 0.001 for the rainfall variable, indicating a significant positive association between rainfall and leptospirosis cases, with a minimum rainfall value of -21.833, a maximum of 25.967 and a median of 0.063. The multiple R-squared value is 0.3265, indicating that approximately 32.65% of the variability in the number of leptospirosis cases can be explained by the variability in rainfall. Conclusion: The study provides additional evidence supporting the influence of rainfall on the occurrence of leptospirosis in Bantul District, Indonesia. The results emphasize the importance of monitoring rainfall patterns as a potential predictive factor for leptospirosis cases in tropical regions like the Bantul District. Efforts to prevent and control leptospirosis in the area should consider environmental factors such as rainfall. However, it is crucial to acknowledge the study’s limitations, including the broad geographical coverage of BMKG data.